India's eucalyptus craze : the God that failed - "Saxena, N. C." (New Delhi, 1994)
Eucalyptus planting on farm lands in India has attracted a great deal of controversy. Whereas the environmentalists have criticised it on the ground that it draws down the water table, thus having negative effect on surroundings crops, foresters who are directly involved with its planting have denied any excess usage by eucalyptus. Several other attributes of the tree are also hotly debated. According to one school, it leads to rapid depletion of soil nutrients, harms Peasants by increasing their dependence on traders, markets and forest bureaucracy, does not produce fodder, reduces area under foodgrains, and affects the landless by cutting down the requirements of wage labour.
Keywords: Eucalyptus industry India